EMPLOYEE MOTIVATION AS A FACTOR OF EFFICIENCY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The concept of motivation, which is the key element of effectiveness in the article, is the role of management in carrying out the motivation function, the motivation for motivation in an organization, the motivation process, the personal and group motivations and their interrelationship. Focuses on the dynamics of employee motivation, the impact of motivation on employee performance, as well as the main types of motivation in the organization, the impact of motivation on the nature of the activity, and the motivation for diversification that motivates it.